Building Student Entrepreneurship Activities Through the Synergy of the University Entrepreneurship Ecosystem - Astuty, Eriana; Yustian, Okky Rizkia; Ratnapuri, Chyntia Ika (Frontiers in Education, 2022)
Student entrepreneurship activities can be a driving force for the emergence of young entrepreneurs. Therefore, universities are making efforts to equip their students with the requisite entrepreneurial knowledge and skills for a conducive university entrepreneurial ecosystem. The present study employs a quantitative approach to survey-type research. The research method uses the explanatory method with research objects, including the internal environment of the institution, external environmental support, student entrepreneurial orientation, student entrepreneurial intentions, and student entrepreneurial activities. Data were collected through online questionnaires, which were randomly distributed to 456 students of seven state universities and 11 private universities across Java and Sumatra, Indonesia. Descriptive and multivariate data analysis with a structural equation model was carried out using the AMOS20 software. The study confirmed a research’s novelty called Entrepreneurship Eclectic Education, which combines several techniques, designs, and methods that have been proven valid, reliable, and feasible for adoption in universities. Such novelty is likely to trigger student performance in their entrepreneurial activities in the university's entrepreneurial ecosystem. This is realized through a synergy between the internal and external environment of the institution that can foster an entrepreneurial orientation, then trigger students' entrepreneurial intentions, which leads to the creation of student entrepreneurship activities. This study yields useful implications for higher education decision-makers for re-orientation of entrepreneurship curriculum, and hence for the creation of a conducive university entrepreneurship ecosystem.